Amending Soil with Rhizobium carrying Biochar Ameliorates Drought Stress on Phaseolus vulgaris: Drought Stress Amelioration in Phaseolus using Biochar - Batool, Aniqa; Rashid, Audil; Aziz, Irfan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
As a consequence of climate change/global warming earth’s agriculture output is under rigorous stress. There is a growing need to develop strategies to cope with these abiotic stresses. Biochar exhibiting many beneficial qualities appeared to alleviate these problems by improving soil fertility by adding carbon and preventing nutrient losses etc. Biochar can also enhance BNF and could be used as a carrier for rhizobium by providing a suitable microenvironment. The current study is aimed to find the ameliorative potential of different biochar types to be used as rhizobium carriers for Phaseolus vulgaris L. exposed to drought stress. Both types of biochar were analyzed for physico-chemical and morphological parameters. Presence of Silicon content remains the key finding for rice husk biochar which was absent in Lantana biochar. Increased C, K, and Ca weight percentages were found in Lantana biochar as compared to their proportions for rice husk biochar. On the contrary, the oxygen content was higher in rice husk biochar as compared to that in Lantana. Phaseolus seeds were used for the pot experiment where stress treatment was applied by FTSW (Fractionable Transpirable Soil Water) technique. One isolated strain along with two types of biochar carrier was applied to the plants in combination with water stress treatment. Plants were analyzed for growth and physiological parameters including plant height, leaf area, biomass, photosynthesis, transpiration rate, stomatal conductance, and water use efficiency, where rice husk biochar responded better than the one obtained from Lantana. Plants responded positively for all the growth as well as physiological parameters when treated in combination with the inoculum for both stress levels i.e., 100% and 60% field capacity F.C. The present study advocates rice husk biochar for its ability to enhance tolerance in Phaseolus against drought stress through its role as an inoculum carrier contributing suitable habitat for the microorganism.